2015
DOI: 10.1002/2014je004712
|View full text |Cite
|
Sign up to set email alerts
|

A multiyear dust devil vortex survey using an automated search of pressure time series

Abstract: Dust devils occur in arid climates on the Earth and ubiquitously on Mars, where they likely dominate the supply of atmospheric dust and influence climate. Martian dust devils have been studied with a combination of orbiting and landed spacecraft, while most studies of terrestrial dust devils have involved manned monitoring of field sites, which can be costly both in time and personnel. As an alternative approach, we describe a multiyear in situ survey of terrestrial dust devils using pressure loggers deployed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 31 publications
1
41
0
Order By: Relevance
“…If it must be done, then ideally an information-theoretic criterion might be used in bin-size selection (e.g. Jackson and Lorenz, 2015), or at least binning be done in some manner well-suited to strongly skewed data e.g. logarithmically (bins of size ratio equal to the square root of two, as used often in the impact cratering community, is one approach).…”
Section: Presentation Of Population Datamentioning
confidence: 99%
See 4 more Smart Citations
“…If it must be done, then ideally an information-theoretic criterion might be used in bin-size selection (e.g. Jackson and Lorenz, 2015), or at least binning be done in some manner well-suited to strongly skewed data e.g. logarithmically (bins of size ratio equal to the square root of two, as used often in the impact cratering community, is one approach).…”
Section: Presentation Of Population Datamentioning
confidence: 99%
“…A preliminary inspection of data from a trial field campaign at El Dorado Playa in Nevada (Lorenz, 2013a) suggested detectable encounter rates (>0.3mbar) on average of 1.3-2.6 per day. More systematic evaluations recording more than a hundred candidate events (Lorenz and Lanagan, 2014) and indeed some thousands of events (Lorenz and Jackson, 2015) have been conducted. This is an author-produced, pre-peer-reviewed version of this article.…”
Section: Vortex Detections In In Meteorological Time Series Datamentioning
confidence: 99%
See 3 more Smart Citations